Patient-reported outcome measures in patients with peripheral arterial disease: a systematic review of psychometric properties. Issue 1 (December 2016) - Poku, Edith; Duncan, Rosie; Keetharuth, Anju; Essat, Munira; Phillips, Patrick; Woods, Helen; Palfreyman, Simon; Jones, Georgina; Kaltenthaler, Eva; Michaels, Jonathan
Abstract Background Peripheral arterial disease (PAD) is generally associated with considerable morbidity and reduced quality of life. Patient-reported outcome measures (PROMs) provide important information about the burden of disease and impact of treatment in affected patients. Objectives The objective of the review was to identify and appraise studies reporting the psychometric evaluation of PROMs administered to a specified population of patients with PAD with a view to recommending suitable PROMs. Methods A systematic review of peer-reviewed English language articles was undertaken to identify primary studies reporting psychometric properties of PROMs in English-speaking patients with various stages of PAD. Comprehensive searches were completed up until January 2015. Study selection, data extraction and quality assessment were undertaken independently by at least two researchers. Findings were presented as tabular and narrative summaries based on accepted guidance. Results Psychometric evaluation of 6 generic and 7 condition-specific PROMs reported in 14 studies contributed data to the review. The frequently reported measure was the SF-36 (n = 11 studies); others included the Walking Impairment Questionnaire (n = 8 studies), EQ-5D (n = 5 studies) and the Vascular Quality of Life Questionnaire (n = 3 studies). Studies included a diverse PAD population and varied in methodology, including approach to validation of PROMs. Conclusions Various PROMs have been validated in patients with PAD but no study provided evidence of a full psychometric evaluation in the patient population. Careful selection is required to identify reliable and valid PROMs to use in clinical and research settings.